2010
DOI: 10.1186/1471-2334-10-147
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of active human cytomegalovirus infection in hematopoietic stem cell transplantation (HLA sibling identical donor): search for optimal cutoff value by real-time PCR

Abstract: BackgroundHuman cytomegalovirus (CMV) infection still causes significant morbidity and mortality after allogeneic hematopoietic stem cell transplantation (HSCT). Therefore, it is extremely important to diagnosis and monitor active CMV infection in HSCT patients, defining the CMV DNA levels of virus replication that warrant intervention with antiviral agents in order to accurately prevent CMV disease and further related complications.MethodsDuring the first 150 days after allogeneic HSTC, thirty patients were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 27 publications
1
25
1
1
Order By: Relevance
“…In a study discussing the clinical utility of CMV realtime PCR in HSCT recipients, the cut-off value for preemptive therapy was determined to be approximately between 2 × 10 4 copies/mL (sensitivity, 80.0%; specificity, 50.0%) and 3 × 10 4 copies/mL (sensitivity, 90.0%; specificity, 70.0%) [27]. However, the optimal cut-off value for the initiation of preemptive therapy remains to be determined [28]. In our study, the onset of CMV infection was always before D+100, emphasizing its role in early post-transplant morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…In a study discussing the clinical utility of CMV realtime PCR in HSCT recipients, the cut-off value for preemptive therapy was determined to be approximately between 2 × 10 4 copies/mL (sensitivity, 80.0%; specificity, 50.0%) and 3 × 10 4 copies/mL (sensitivity, 90.0%; specificity, 70.0%) [27]. However, the optimal cut-off value for the initiation of preemptive therapy remains to be determined [28]. In our study, the onset of CMV infection was always before D+100, emphasizing its role in early post-transplant morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] The clinical utility of real-time PCR tests to guide preemptive therapy in transplant recipients at high-risk for CMV infection has been mainly studied in hematopoietic stem cell transplant recipients (HSCTR) and in SOT recipients (SOTR) at highrisk. [14][15][16][17][18] Surprisingly, some studies have shown a higher incidence of CMV disease in SOTR at low-risk of CMV. [19][20][21][22] In addition, results showed significant differences between different techniques used to determine the CMV viral load and therefore results cannot be compared.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the widespread use of quantitative PCR, there is no consensus regarding the CMV level at which preemptive therapy should be initiated(9-11). Some studies have suggested a threshold of 500 copies/mL, others 1000 copies/mL, while others suggest different thresholds dependent on recipient risk(12-15). This lack of consensus translates into significant heterogeneity in clinical practice.…”
Section: Introductionmentioning
confidence: 99%